PERANCANGAN ALAT MONITORING KUALITAS UDARA SECARA REAL-TIME DI KAWASAN PASAR BUNGO - Mutia Hariza Lubis; Upik Nurbaiti; Fianti Fianti (EnviroScienteae, 2021)
The market area in Bungo Regency is an area with community activities and a high number of vehicles so that it has an impact on the air quality around the area. This study aims to design a monitoring tool as a cost-effective facility in order to monitor air quality as a first step to minimize air pollution in the Bungo market area. Air quality is assess through temperature and humidity measured using the DHT11 sensor, smoke levels in the air are measured using the MQ2 sensor, and light intensity is measured using the LDR module.